How a media image is created - A case study of Electric Power Industry of Serbia - Cebalović, Momčilo (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2015)
The media significantly influence the creation of public sector image in Serbia, especially public companies whose sale was announced by the government representatives. For this reason, a quantitative and qualitative analysis of media reporting was performed on ten most influential daily newspapers (Politika, Blic, Informer, Kurir, Nase novine, Vecernje novosti, Dnevnik, Danas, ALO and Pregled) and three weekly ones (NIN, Vreme and Novi magazin) throughout two periods - from 28.4 to 15.5.2014 and from 1.6 until 23.6.2014. The aim of the study was to determine whether the media create image of Public Enterprise Electric Power Industry of Serbia (EPS) which should be privatized, if there are trends in creating that image and which sources of information presented to public are most visible. By analyzing the content we searched for an answer to whether these media apply investigative reporting and use analytical articles. The analysis revealed that the media strongly influence the image creation that EPS needs to be sold, that this is a tendency and that media give more space to advocates of this idea. During the studied periods there were 59 news releases, of which 31 (52.5%) advocated for the sale, against were 15 (25.4%), and neutral 13 news releases (22.1%). From a total of 70 statements, privatization has also been suggested in 38 statements (54.3%), 23 statements (32.8%) were against, while there was 9 neutral statements (12.9%). The research has demonstrated that by superficial reporting media misinform the public, use half-truth and spinning and that such writings contain elements of propaganda.
Keywords: EPS; public; public sector; privatization; media; disinformation; media spinning; propaganda